A study of dampness on flat roof at Heritage Mosque in Perak / Nur Asma’ Ul- Husna Baharuddin - Baharuddin, Nur Asma’ Ul- Husna (2016)
Heritage building in Malaysia are very unique and have their own culture values that will remind with past. Besides that, the heritage mosque is a building that has long been built and has a unique architecture. According to Johar(2011), heritage mosque same like old building of historic that other has also made significant contributions in the history of the country . The building must be maintained from defects to protect their aesthetic values. It is a quite natural that as buildings aged; they will be exposed to serious building defects. Repairing works should be carried accurately with the kind of defects and its must not intervene the values of the cultural heritage (Mustafa, 2011).